Synthesis and Biocidal Nature of Oxamic Acids - Singh, Lal; Kumar, U.; Singh, J.; Sharma, R.C. (Asian Journal of Chemistry, 2010)
Synthesis of seven oxamic acids, viz., N-p-nitrophenyl oxamic acid, N-p-chlorophenyl oxamic acid, N,N-o-phenylene dioxamic acid,N,N´-m-phenylene diamine dioxamic acid, No- phenol oxamic acid, N-pyridino-p-carboxy oxamic acid and N-pyrazole oxamic acid was carried out by refluxing the pure aromatic amino compounds with anhydrous diethyloxalate and characterized by their physico-chemical studies. All compounds were biocidal in nature.